2016
DOI: 10.1080/14767058.2016.1187126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and its risk factors among pregnant women in Khorramabad (Iran) 2010–2014

Abstract: Staff working at different parts of health care centers were advised to pay more attention to this problem. They should also try to control and treat anemia by regular distribution of iron supplements among women referred to health care centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
6
1
2
Order By: Relevance
“…This study revealed anemia (Hb<11 g/dl) in 8.2% of women in first trimester and higher than one-quarter of women in third trimester of pregnancy. Similarly, 16.8% of pregnant women were anemic in Iran (11). We found lower frequency of anemia in Iranian pregnant women compared to some other developing countries.…”
Section: Discussionmentioning
confidence: 42%
“…This study revealed anemia (Hb<11 g/dl) in 8.2% of women in first trimester and higher than one-quarter of women in third trimester of pregnancy. Similarly, 16.8% of pregnant women were anemic in Iran (11). We found lower frequency of anemia in Iranian pregnant women compared to some other developing countries.…”
Section: Discussionmentioning
confidence: 42%
“…Cette prévalence de 39,8% est superposable à celle deDesalegn et alen Ethiopie et Taner et al en Turkie qui ont retrouvé respectivement 41,9% et 41,6% [ 7 , 11 ]. Des prévalences plus basses ont été rapportées en Iran (16,8%), en Ouganda (22,1%) et en Grande Bretagne (24,4%) [ 3 5 ]. Selon les statistiques de l’OMS, la prévalence de l’anémie est liée au développement et reste plus basse dans les pays développés.…”
Section: Discussionunclassified
“…Il s’agit d’un trouble de gravité variable auquel sont exposées 17 à 31% des femmes enceintes dans les pays développés et 52,8 à 61,3% en Afrique au Sud du Sahara [ 1 ]. Quelques études consultées rapportent des prévalences de 16,8%, 22,1%, 24,4%32,8%,41,6% et 100% respectivement en Iran, Ouganda, en Grande Bretagne,en Ethiopie, en Turkie et Inde [ 3 8 ]. Les facteurs de risques de l’anémie en grossesse varient considérablement d’un milieu à l’autre.…”
Section: Introductionunclassified
“…Anemia classification was performed based on world health organization guidelines. Subjects with hemoglobin level lower than 11 g/dL were divided in exposed group and subjects with hemoglobin level higher than 11 g/dL were divided into un-exposed group (6,11).…”
Section: Study Populationmentioning
confidence: 99%